Copper-Bisbenzimidazole Complexes as Biomimetic Catalysts in Organic Transformations - Jain, Manisha; Yadav, Shilpa; Mansi; Misra, Neeti; Khanna, Pankaj; Khanna, Leena (Mini-Reviews in Organic Chemistry, 2024)
Copper complexes have biological applications as well as catalytic importance in performing organic reactions. Besides finding utilities in metalloproteins, enzymes, or molecular magnetism, they have been used extensively as catalysts in the formation ofcarbon–carbon or carbon– heteroatom bonds, in addition to many other reactions. This has been achieved by the rational selection of the organic ligands with suitable coordination sites for attaining ideal geometries. The binding of one such organic ligand, bisbenzimidazole, with copper results in complexes with varied shapes, structures, and activities, enhancing their catalytic potential and hence useful applications. This review describes the catalytic applications of bisbenzimidazole based copper (II)/(I) complexes in various useful organic transformations. It also provides an in-depth knowledge of the mechanistic pathways of the transformations involving copper complexes and their multipurpose utility as catalysts, which may help in the development of improved copper catalysts for the future.
Keywords: copper complex